Boundary crossing organizations in regional innovation systems. Issue 1 (4th March 2013) - Kilpatrick, Sue; Wilson, Bruce
Abstract Innovation policy in many countries recognizes the significance of place‐based innovation systems. Australia's innovation policy has incentives to bring universities and businesses together, but lacks place‐based mechanisms to achieve this. Four case studies of regional intermediary organizations in Melbourne, Australia are examined to understand their role in enabling collaboration between university and industry. Each manages networks, facilitates collaboration, develops a shared direction and acts as a regional 'door' to broader systems. The ability of intermediary organizations to cross boundaries between knowledge generating and innovating entities is key to the cohesion and effective operation of the regional innovation systems.